Examining the Research Criteria for Traumatic Encephalopathy Syndrome in Middle-Aged Men From the General Population Who Played Contact Sports in High School - Iverson, Grant L.; Merz, Zachary C.; Terry, Douglas P. (Frontiers in Neurology, 2021)
Objective: There are no validated or agreed upon diagnostic clinical criteria for chronic traumatic encephalopathy or traumatic encephalopathy syndrome. This study examines the leading research criteria for traumatic encephalopathy syndrome (TES) in middle-aged men in the general population. Method: Participants were 409 men between the ages of 35 and 55 recruited through an online crowdsourcing platform. Participants provided demographic information, medication history, concussion history, contact sport history, current medication use, and current symptoms. Research criteria for TES were applied to the sample. Results: Over half of the total sample met TES symptom criteria (56.2%), without applying the neurotrauma exposure criteria. Those with 4+ prior concussions had higher rates of meeting TES criteria compared to those with 0–3 prior concussions, but the results were not statistically significant (69.8 vs. 54.6%; χ2 = 3.58, p = 0.06). Exposure to contact sports was not related to higher rates of TES (ps ≥ 0.55). In a binary logistic regression predicting the presence of mild or greater TES, significant predictors were sleep difficulties [Odds ratio (OR) = 6.68], chronic pain (OR = 3.29), and age (OR = 1.04). Neurotrauma exposure was not a significant predictor (p = 0.66). When analyzing those with no prior concussions or contact sport histories (n = 126), 45.2% met symptom criteria for mild or greater TES; chronic pain and sleep difficulties were associated with a higher prevalence of meeting criteria for TES in this subgroup (ps < 0.001). Conclusions: Men who participated in contact sports in high school or college were not more likely to meet criteria for TES than men who participated in non-contact sports or no sports. In a multivariable model, sleep problems and chronic pain were predictive of meeting the symptom criteria for TES, but the repetitive neurotrauma exposure criterion was not a significant predictor of meeting the TES symptom criteria.